The real ethical problem with metaverses - Munn, Nick; Weijers, Dan (Frontiers in Human Dynamics, 2023)
Many philosophers hold that the human risks associated with the development and use of metaverses arise primarily from their status–they are unreal in ways that make the experiences within them meaningless and thereby less prudentially valuable (Shea, 2017). This purported unreality is not merely a result of the virtual or intangible nature of metaverses. Rather, it arises from the idea that, regardless of the experiences, interactions, and affordances of metaverses, what we do in these spaces is somehow different and impoverished compared to what we do in the physical world. Those who think this believe that our behaviour and interactions within metaverses are inferior to our behaviours and interactions in the physical world in a way that confers less value on the lives of those engaging regularly within metaverses. Some commentators worry that repeated exposure to these impoverished virtual experiences will somehow dehumanise us or make us worse at offline interactions, and certainly reduce the amount of time we have for more meaningful real-world pursuits (Brey, 1998; Lavoi et al, 2020; Kaimara et al, 2022). If true, this would be a serious concern for metaverse-evangelists and users. However, in this article we will argue that it is not so – in fact, metaverses are morally relevantly similar to the physical world, and capable of providing most of the experiences and interactions we find in the physical world – whether positive or negative. However, metaverses are not without risks. We claim that the real ethical problem with metaverses arises, in their current instantiation, from the risks involved in their development as commercial enterprises, locking users into particular infrastructures and placing power over the continuation or termination of the metaverse in the hands of a corporate entity that has goals and motivations independent of those of the users of the metaverse.